Definition of dynamic system dimension on an output signal through correlation dimension in a pseudo-phase space - Matviychuk, Yaroslav (Видавництво Львівської політехніки, 2005)
The universal method is described which allows to receive a reliable estimation of a nonlinear system dimension only by one scalar output signal, at this the estimation does not depends on what an output signal of the system is used.
Keywords: dynamical system; model dimension; correlation; pseudo-phase space